(untitled) (Indian Journal of Animal Production and Management, 2015)
A study was conducted to investigate the effect of different anti-stress agents on the growth performance and survivability of broilers. Four hundred and eight day old chicks were randomly divided into two groups and reared under cage and deep litter system respectively. Each group was further divided into 4 sub-groups of 51 chicks each and were given different anti-stress agents along with standard broiler ration. Group T 1 & T 5 were treated as Control, Group T 2 & T 6 were treated with Zeetress , Group T 3 & T 7 were treated with Glucose and Group T 4 & T 8 were treated with honey under cage and deep litter system respectively. The body weight gain and Feed Conversion. Ratio was significantly (P<0.01) higher in Zeetress treated groups T2 and T6 both for a period of 42 days over glucose and honey treated groups T3,T7 and T4, T8 respectively. The average body weight was significantly (P<0.01) higher in cage system (45.30+0.32) than deep litter system (44.76 + 0.28). The overall mortality varied from 3.92% (honey treated) to 7.84% (control) under cage system while.82% (honey treated) to 5.88% (control & glucose) under deep litter system of management. Antistress agent Zeetress has better effect on growth performance and survivability of broiler chickens followed by glucose and honey over control.